2022
DOI: 10.1101/2022.08.30.505732
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coenzyme A governs proinflammatory macrophage metabolism

Abstract: The magnitude and duration of Toll-like receptor (TLR)-dependent macrophage proinflammatory responses are tightly regulated. Chronic TLR signaling drives tolerance, an immunosuppressed state of innate immune memory. Understanding of this regulation is incomplete. Here, we demonstrate that direct Coenzyme A (CoA) supplementation both reverses tolerance, and enhances TLR-dependent macrophage proinflammatory responses. Synergizing with TLR-driven glycolysis, CoA enhances glucose entry into the mitochondrial TCA c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 119 publications
1
3
0
Order By: Relevance
“…Here we show that CoA is a putative DAMP that primes macrophages for alternative activation and supports resolution via extrinsic, weak agonism of pro-inflammatory TLR4 and MyD88 signaling. This aligns with recent reports that show CoA increases the expression of proinflammatory genes such as Il1b, Tnf and Nos2 in mouse and human macrophages, an effect lost in mice with simultaneous genetic ablation of TLR2, TLR4, and the TLR chaperone protein Uncb93b1 54 . The data presented here that CoA itself is a TLR4 agonist likely explains the effect, rather than CoA having an indirect effect on the pro-inflammatory response via altered mitochondrial metabolism.…”
Section: Various Cellular Metabolites Including Lipids Atp and Uric A...supporting
confidence: 92%
“…Here we show that CoA is a putative DAMP that primes macrophages for alternative activation and supports resolution via extrinsic, weak agonism of pro-inflammatory TLR4 and MyD88 signaling. This aligns with recent reports that show CoA increases the expression of proinflammatory genes such as Il1b, Tnf and Nos2 in mouse and human macrophages, an effect lost in mice with simultaneous genetic ablation of TLR2, TLR4, and the TLR chaperone protein Uncb93b1 54 . The data presented here that CoA itself is a TLR4 agonist likely explains the effect, rather than CoA having an indirect effect on the pro-inflammatory response via altered mitochondrial metabolism.…”
Section: Various Cellular Metabolites Including Lipids Atp and Uric A...supporting
confidence: 92%
“…The contribution of mitochondrial activity to antigen recognition and the efficacy of immunotherapy is still debated ( Bonifaz et al, 2014 ; Harel et al, 2019 ; Jones & Divakaruni, 2020 ; Yin & O’Neill, 2021 ). In macrophages, CoA administration enhances acetyl-CoA–mediated epigenetic activation of pro-inflammatory gene transcription and boosts TAM antitumor activity in breast cancer ( Timblin et al, 2022 Preprint ). Although dendritic cells require enhanced mitochondrial activity for the acquisition of antigen-presenting capacity in vitro, we failed to detect any Pant-mediated enhancement in OVA presentation to OT1 T cells by cDC1 extracted from Pant-treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of mitochondrial activity to antigen recognition and e cacy of immunotherapy is still debated (43) (44, 45) (46). In macrophages, CoA administration enhances acetyl-CoA-mediated epigenetic activation of pro-in ammatory gene transcription, and boosting TAM anti-tumor activity in breast cancer (17). Similarly, in vitro, dendritic cells require enhanced mitochondrial activity for the acquisition of antigen-presenting capacity (47).…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that VNN1-mediated restoration of vitB5 levels in a tumor microenvironment could paracrinally activate immune responses. Interestingly, it was recently found that vitB5 or CoA could boost in vitro macrophage or CD8 + T lymphocyte maturation, respectively (16,17). We therefore tested whether, independently of VNN1 expression, enhancing vitB5 levels via pantethine administration to a tumor-bearing mouse might simultaneously limit tumor growth while boosting anti-tumor immunity.…”
Section: Introductionmentioning
confidence: 99%